Multi-agency public protection arrangements and youth justice - Baker, Kerry 1971-; Sutherland, Alex 1977- (Researching criminal justice series, 2023)
This report provides a detailed exploration of MAPPA policy and practice in order to prompt further debate about the implications of the risk paradigm for young people and youth justice practitioners